Nanog RNA‐binding proteins YBX1 and ILF3 affect pluripotency of embryonic stem cells. (19th June 2016) - Guo, Chuanliang; Xue, Yan; Yang, Guanheng; Yin, Shang; Shi, Wansheng; Cheng, Yan; Yan, Xiaoshuang; Fan, Shuyue; Zhang, Huijun; Zeng, Fanyi
Abstract: Nanog is a well‐known transcription factor that plays a fundamental role in stem cell self‐renewal and the maintenance of their pluripotent cell identity. There remains a large data gap with respect to the spectrum of the key pluripotency transcription factors' interaction partners. Limited information is available concerning Nanog‐associated RNA‐binding proteins (RBPs), and the intrinsic protein–RNA interactions characteristic of the regulatory activities of Nanog. Herein, we used an improved affinity protocol to purify Nanog‐interacting RBPs from mouse embryonic stem cells (ESCs), and 49 RBPs of Nanog were identified. Among them, the interaction of YBX1 and ILF3 with Nanog mRNA was further confirmed by in vitro assays, such as Western blot, RNA immunoprecipitation (RIP), and ex vivo methods, such as immunofluorescence staining and fluorescent in situ hybridization (FISH), MS2 in vivo biotin‐tagged RNA affinity purification (MS2‐BioTRAP). Interestingly, RNAi studies revealed that YBX1 and ILF3 positively affected the expression of Nanog and other pluripotency‐related genes. Particularly, downregulation of YBX1 or ILF3 resulted in high expression of mesoderm markers. Thus, a reduction in the expression of YBX1 and ILF3 controls the expression of pluripotency‐related genes in ESCs, suggesting their roles in further regulation of the pluripotent state of ESCs.